1981
DOI: 10.1073/pnas.78.6.3536
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase inhibitor-inducing factor activity in tomato leaves resides in oligosaccharides enzymically released from cell walls

Abstract: The synthesis andaccumulation of proteinase inhibitor I in excised tomato leaves can be induced with oligosaccharides obtained by fungal endo-a-1,4-polygalacturonase digestion of a pectic polysaccharide (Mr 5000-10,000) isolated from tomato leaves. Active oligosaccharides were-also released from isolated tomato leaf cell walls by endopolygalacturonases partially purified from tomato plants. It.is suggested that oligosaccharides, released from plant cell wall pectic polysaccharides by either endogenous or exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(83 citation statements)
references
References 13 publications
1
81
0
1
Order By: Relevance
“…OGAs derived from plant cell walls (Bishop et al, 1981) and chitosan, which is a mixture of glucosamine oligomers derived from fungal cell walls , are elicitors of defensive genes in a variety of plant systems (Ryan and Farmer, 1991;John et al, 1997). The inducing activities of both OGA and chitosan are considered to be receptor mediated (Felix et al, 1993;Ebel, 1998) and, in tomato leaves, like systemin, they activate genes through the octadecanoid signaling pathway (Doares et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…OGAs derived from plant cell walls (Bishop et al, 1981) and chitosan, which is a mixture of glucosamine oligomers derived from fungal cell walls , are elicitors of defensive genes in a variety of plant systems (Ryan and Farmer, 1991;John et al, 1997). The inducing activities of both OGA and chitosan are considered to be receptor mediated (Felix et al, 1993;Ebel, 1998) and, in tomato leaves, like systemin, they activate genes through the octadecanoid signaling pathway (Doares et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…During wounding, oligosaccharides are released from the wounding site in two ways: 1) by mechanical destruction of the cell, followed by the discharge of the contents of the cell, and 2) by induction of endogenous polygalacturonases. Oligosaccharides released from wounding sites have been suggested to have a role in signaling, but aside from that they are also an important resource for the plant that needs to be recovered (35,36). In addition, invertases are also induced in wounded tissues, for instance, in wounded taproots of carrots (37).…”
Section: Discussionmentioning
confidence: 99%
“…This substance must: (i) be synthesized quickly in response to damage, (ii) induce electrical reactions, and (iii) propagate easily in plants. Oligosaccharides of broken cell walls, 66 systemin, 67 jasmonate, 18,68 salycilic acid, 69 ethylene 19,70 and abscisic acid 1,2 are considered to be potential wound substances. In recent studies, 71 hydrogen peroxide (H 2 O 2 ) has been shown to propagate from the damage zone and induce an electrical reaction.…”
Section: Mechanism Of Variation Potential Propagationmentioning
confidence: 99%